Desenvolvimento de complexos polipiridínicos de rutênio (II): estudos de reatividade e potencial biológico - Galhardo, Patrícia Helenita Rocha Martins (2024)
Studies involving ruthenium polypyridine complexes has brought interest of the scientific community because they generally present low toxicity compared to other metallopharmaceutical candidate systems. Associated with this characteristic, there are appealing ligands that can be incorporated into these systems, such as those based on phenazine type (e.g., dppz = dipyrido[3,2-a:2',3'-c]fenazine) and bipyridine = 2,2’ bipyridine, a known DNA intercalator, and nitric oxide, which has vasodilatory and antiparasitic properties, among others. Thus, in this work, these properties were combined, where three ruthenium polypyridine complexes were synthesized: precursor [Ru(bpy)(dppz)Cl2] (PR), and compounds Na[Ru(bpy)(dppz)(SO3)(NO2)] (PR01) and [Ru(bpy)(dppz)(SO3)(NO)](PF6) (PR02). These compounds were characterized by spectroscopic techniques, electrochemistry, elemental analysis and mass spectrometry. Acid-base titration of the compound PR02 showed evidence of two pH-dependent chemical equilibria at pHs 5.94 and 9.16, attributed to the protonation of the nitrogen of the dppz ligand and interconversion of NO+ to NO2-, respectively. Reactive oxygen species (ROS) generation tests showed the formation of superoxide ion at a low concentration of the compound PR02 (1 µmol L-1). The association constants (Kb) with DNA were obtained, whose values are in the order of 104 for PR complex and 105 for PR01 and PR02 complexes. Agarose gel electrophoresis measurements showed interaction/cleavage of DNA after light irradiation, with enhancement of DNA cleavage with increasing concentrations. PR02 complex also had its ability to cleave DNA in the presence of H2O2 inhibited with tiron (suppressor of O2•-) and cPTIO (NO/HNO suppressor). Circular dichroism studies supported the interaction of the PR, PR01 and PR02 complexes with double-stranded and G-quadruplex DNA. Biological studies showed moderate vasodilatory activity for the PR02 complex (IC50 = 25 µmol L-1). The antimicrobial action was also investigated, where promising activity of the compound PR02 was observed. Furthermore, this compound showed the ability to reduce bacterial biomass and synergistic antibacterial activity in combination with antibiotics of clinical use. Hemolytic activity assay showed that the PR, PR01 and PR02 complexes did not cause hemolysis at the maximum concentrations studied, initially suggesting a safety for use. Altogether, these results indicate PR02 as a promising drug candidate that deserve further biological studies.